The Retrogenesis Model in Alzheimer’s Disease: Evidence and Pract ical Applications - Ahmed, Saeed; Kaur, Amandeep; Venigalla, Hema; M. Mekala, Hema; K. Brainch, Navjot; Ayub, Shahana; Hassan, Mudasar (Current Psychiatry Reviews, 2017)
Background: The increasing number of people living with Alzheimer’s disease (AD) constitutes a growing global concern. At present, nearly 44 million people suffer from AD worldwide, and these numbers are expected almost to double every 20 years. Given its high prevalence and growing incidence, AD is one of the top causes of disabilities in later life, and this takes an enormous toll on the caregivers. Importance: It is tremendously important to explore new ways of understanding AD, as this may improve the management of this growing medical, socio-economic, and public health care burden. Conclusion: Evidence suggests that AD may evolve through the unique process of ‘retro-genesis’; a decline that mirrors, in reverse order, brain development that occurs from birth. The retro-genesis hypothesis distinguishes distinct stages, each one linked to levels of cognitive functioning in developing children. The understanding of clinical correlations and practical applications of retrogenesis theory may help caregivers to recognize different stages of AD, and to provide better care with less burden.
Keywords: dementia